2012
DOI: 10.1002/bse.1728
|View full text |Cite
|
Sign up to set email alerts
|

Green Buildings and Organizational Changes in Italian Case Studies

Abstract: International policies indicate the building sector as one of the most promising for sustainable development. According to the Intergovernmental Panel on Climate Change (IPCC), it has the greatest and cheapest potential for delivering significant greenhouse gas emission reduction. However, early experiences of sustainable construction have shown that both a social and a technical transition are required. Consequently, the changes in organizational aspects of firms involved in construction represent an urgent r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 56 publications
1
63
0
Order By: Relevance
“…Such benefits include greater risk-sharing, less project risk, the transfer of practices and processes to other projects, improved cooperation, mutual understanding, improving overall competitiveness and increased customer satisfaction [46]. Albino and Berardi [75] found that limiting risks was one of the reasons why contractors select suppliers for green projects. One of the objectives for partnering was the early involvement of suppliers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such benefits include greater risk-sharing, less project risk, the transfer of practices and processes to other projects, improved cooperation, mutual understanding, improving overall competitiveness and increased customer satisfaction [46]. Albino and Berardi [75] found that limiting risks was one of the reasons why contractors select suppliers for green projects. One of the objectives for partnering was the early involvement of suppliers.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, firms can benefit from suppliers' knowledge in solving unforeseen problems in green projects [74] by establishing cooperative innovation [20]. Albino and Berardi [75] show that contractors consider supplier knowledge and ability to "co-make" green projects.…”
Section: Procurement Methods In Green Projectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, while it is widely recognised that the development of better buildings is a major challenge for a range of sustainability issues-not least of all, global climate change-many have noted that commercial buildings often receive more attention than residential buildings (e.g., [26], p. 388). Indeed, this is notwithstanding the fact that the latter is responsible for the majority of the building stock and associated environmental impacts (e.g., [27]).…”
Section: Discussionmentioning
confidence: 99%
“…For project-based construction organizations, construction projects are their core business [24]. Construction project process refers to "a series of activities of planning, realization and direction through which materials and equipment are assembled into a building" [25]. Such process of delivering a construction project from the project supplier to its client is a value generation process [26], which is the operational business process of a construction organization according to Davenport and Short's [20] classification and terminology of business process.…”
Section: Primarymentioning
confidence: 99%